Aromatic Plants of Kenya IV: Volatile and Some Non-Volatile Constituents of the Stem Bark of Synadenium Compactum N.E. Br. Var. Compactum (The East and Central African Journal of Pharmaceutical Sciences, 2020)
The essential oil isolated by hydrodistillation from the stem-bark of Synadenium compactum N.E. Br. var. compactum (0.2 %) was analysed by GC and GC-MS. Fifty five compounds constituting about 89.9 % of the oil were separated from the oil and many of them were identified. The ,major constituents were a-- and p-selinene (29.6 % and 19.3 %, respectively). The petroleum spirit extract of the stem bark yielded friedelinol, epifriedelinol and friedelin.
Keywords: Synadenium compactum, essential oil, a- and J3-selinene, friedelinol, epifriedelinol and friedelin.